The effect of variable light intensity in luminescent-netting pots on the catch of snow crab (Chionoecetes opilio) - Colin C.H. Frank; Shannon M. Bayse (Aquaculture and Fisheries)
The use of light in pots has been shown to increase snow crab catch rates in eastern Canada and the Barents Sea, where better fishing efficiency could result in less fuel consumption, and financial and ecological benefits. However, some light characteristics necessary for maximizing efficiency have yet to be researched. The purpose of this study was to determine if there is a change in catch per unit effort (CPUE; number of snow crab per pot) and size selectivity of snow crab with varying light intensity. Three types of experimental luminescent-netting pots were used, each type with a different level of light intensity via the amount of phosphorescent strands woven into the pot netting, (either 2-, 4-, or 6-strands) and were compared to the traditional pot used in the fishery. There were mixed results among treatments, with the 2-strand pot catching fewer snow crab <103 mm carapace width (CW) and more snow crab ≥103 mm CW than the traditional pots, but overall, had a lower CPUE for legal and sub-legal sized males (14.8 and 3.1 per pot, respectively) than the traditional (16.1 and 5.5 per pot, respectively) when considering all size classes. When compared to the traditional, the 4-strand pot caught more legal and sub-legal (CPUE of 18.8 and 8.0 per pot, respectively) snow crab in terms of CPUE but caught fewer commercial snow crabs from 95 to 98 and 103–113 mm CW. The brightest intensity pots (6-strand) showed no significant difference in CPUE or size selectivity in comparison to the traditional. Increased light intensity pots either had no effect on snow crab capture (6-strand) or produced unwanted results (loss of commercial sizes, increase in sub-legal sizes). Conversely, the 2-strand pot showed decreases in juvenile crab catch and increases in the catch of the most valuable size-classes observed, which are attractive results to fisheries managers and harvesters, respectively. These results, combined with a large price increase, suggest that higher light-intensity pots are not attractive for the commercial fishery.